Evaluasi Kebijakan Pemilihan Kepala Daerah Di Provinsi Nangroe Aceh Darussalam (Sebagai Kajian Evaluasi Formatif) - Sitorus, Monang; Jaswad, Jaswad (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2007)
By the end of 2016, the societ of Aceh have held a local democracy party to chose local leader that is a direct election. Election of regional leader is the directly arranged in law 11 year 2006, about governance of Aceh and Qanun (Perda) No 7 year 2006 with implementor KIP (Independent commision of Electio) or a kind of KPUD (Commission of General Election Area). Implementor of Pilkada in Aceh represent unique something that in Indonesia, because candidate of permit from independent, and implementor also the monitoring Uni Europe.